Central Venous Pressure Drop After Hypovolemic Phlebotomy is a Strong Independent Predictor of Intraoperative Blood Loss During Liver Resection - Ryckx, Andries; Christiaens, Claudine; Clarysse, Mathias; Vansteenkiste, Franky; Steelant, Pieter Jan; Sergeant, Gregory; Parmentier, Isabelle; Pottel, Hans; D’Hondt, Mathieu (Annals of surgical oncology, 2017)
Background Intraoperative hypovolemic phlebotomy (HP) has been suggested to reduce central venous pressure (CVP) before hepatectomy. This study aimed to analyze the impact of CVP drop after HP on intraoperative blood loss and postoperative renal function. Methods A retrospective review of a prospective database including 100 consecutive patients (43 males and 57 females; mean age, 65 years; range 23–89 years) undergoing liver resection with HP was performed. The primary outcome variable was estimated blood loss (EBL), and the secondary outcome was postoperative serum creatinin (Scr). A multivariate linear regression analysis was performed to identify predictors of intraoperative blood loss. Results The median CVP before blood salvage was 8 mmHg (range 4–30 mmHg). The median volume of hypovolemic phlebotomy was 400 ml (range 200–1000 ml). After HP, CVP decreased to a median of 3 mmHg (range –2 to 16 mmHg), resulting in a median CVP drop of 5.5 mmHg (range 2–14 mmHg). The median EBL during liver resection was 165 ml (range 0–800 ml). The median preoperative serum creatinin (Scr) was 0.82 g/dl (range 0.5–1.74 g/dl), and the postoperative Scr on day 1 was 0.74 g/dl (range 0.44–1.68 g/dl). The CVP drop was associated with EBL ( P < 0.001). There was no significant impact of CVP drop on postoperative Scr. Conclusion A CVP drop after HP is a strong independent predictor of EBL during liver resection. The authors advocate the routine use of HP to reduce perioperative blood loss and transfusion rates in liver surgery. As a predictive tool, CVP drop might help surgeons decide whether a laparoscopic approach is safe.